Structural insights into thyroid hormone transporter MCT8 - Jiaxin Tan; Yuan Xiao; Fang Kong; Jiawei Qian; Angqi Zhu; Chuangye Yan (Nature Communications)
Abstract Thyroid hormones (THs), including T4 (3,5,3′,5′-tetraiodo-L-thyronine) and T3 (3,5,3′-triiodo-L-thyronine), play critical roles in regulating tissue development and basal metabolism. Monocarboxylate transporter 8 (MCT8) is a key player in TH transport, known for its high specificity and affinity for THs and its direct association with Allan-Herndon-Dudley syndrome (AHDS) caused by pathogenic mutations. In this study, we present the cryo-EM structures of human MCT8 bound to the substrate T3 or the inhibitor silychristin, both in an outward-open conformation at resolutions of 3.0-3.2 Å. MCT8 forms a homodimer with a lipid molecule positioned at the dimerization interface. The carboxyl group of T3 is recognized by Arg371, while its three iodine atoms interact with distinct hydrophobic cavities. Silychristin is also recognized by Arg371, competing with T3 for binding. Complemented by structure-guided biochemical analyses, our research elucidates the mechanisms of substrate recognition and transport, as well as the mode of action of the inhibitor silychristin. These findings may offer insights for developing targeted therapies for TH-related disorders.